Prevalent practices amongst healthcare professionals in paediatric settings in using medical interpreters for families with limited national language proficiency: A narrative scoping review - Yewande Ogunnaike; Abbey Hyde; Suja Somanadhan (Elsevier, 2022)
Background: Where language barriers exist, trained medical interpreters provide more accurate and comprehensive communication between clinicians and service users compared to ad hoc interpreters or no interpreter at all. The nature and extent of research evidence about when and how medical interpreters are used by health professionals in paediatric settings to mediate communication with families who do not speak the national language proficiently have not yet been published. Aim: To examine the potential size and scope of available research literature about the prevalent practices of healthcare professionals in using medical interpreters in paediatric settings for families with limited national spoken language proficiency. Methods: We used an established framework for scoping reviews, including suggested modifications by JBI. Precise eligibility criteria were identified, and a comprehensive search strategy was applied. Sources of evidence were confined to primary research that spoke specifically to the research question. The process of study selection and results are presented narratively and in tabular form. Two reviewers independently engaged in the screening process, and two reviewers undertook a full paper review of the included articles, with a third consulted where an additional opinion was required. Results: We included 21 studies published between 2000-2022, most using (quantitative) survey methods. Key results captured in six themes are as follows: medical interpreters tended to be underused by health professionals, especially nurses; time was the greatest impediment to their use, but so too were difficulties with the perceived quality of interpreter services; technology was used for medical interpreting at some study sites with mixed responses; use of unauthorised interpreters was widespread; language barriers impacted on the care provider and family relationship; and cost of interpreter services tended not to be reported as a barrier to their use. Conclusions: Further scholarship is needed to understand the use of medical interpreter services with reference to the complexity of health work, as well as the social context of inequality for many families with limited national language proficiency accessing paediatric healthcare. Recent developments in video technology offer promise in improving interpreter use but require oversight for quality. We have highlighted the need for better training for and regulation of medical interpreters and clinical guidelines on the use of interpreters by healthcare professionals.